SUBJECTIVE WELL-BEING PADA GURU TK MASYITOH IV LAWEYAN SURAKARTA (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to look at the general description of subjective well-being in terms of cognitive and affective aspects, and the contribution of the factors forming subjective well-being to the level of subjective well-being in TK Masyitoh IV Laweyan Surakarta teachers. Subjective well-being is explained as a person's subjective evaluation of his life, including overall satisfaction with life which is characterized by high positive affect and low negative affect (Diener, 1984). The method used in this study was a qualitative method, using semi-structured interviews. The main informants in this study were two teachers of TK Masyitoh IV Laweyan Surakarta, supporting informants in this study were administrators of TK Masyitoh IV Laweyan Surakarta, numbering one person and one student's parents. The results showed that the average subjective well-being of TK Masyitoh IV Laweyan Surakarta teachers was quite high. On average, TK Masyitoh IV Laweyan Surakarta teachers like their life and feel that everything is going well. For further research that is interested in conducting research with the same theme, it is expected to deepen the factors that influence subjective well-being in kindergarten teachers such as gender and age. Respondents who were studied also need to be added with varied backgrounds.